ASR and RE - Jensen, Tim (Journal of the Irish Society for the Academic Study of Religions, 2016)
As a university discipline, the academic study of religions (ASR) has produced a critical approach to the study of religion which is (or ought be), I think, of fundamental importance for a modern secular and enlightened democratic state. However, the "study-of-religions" approach has percolated with limited success into society at large as well as into the primary and secondary educational systems of Western democracies. Too often so-called religious education (RE) really is religious or confessional, and even so-called non-confessional RE is, mostly if not always, mixed with crypto-confessional approaches, inculcation of moral values (not least those claimed to be Christian) and the promoting of religion as a resource for a more "spiritual" approach to life. While these goals may be in line with the traditional use of the public school as the key instrument of the (nation-) state to try to confer its ideology to (future) citizens, it is not compatible with the ideals of the academic study of religion, nor with the ideals and ideas of the present writer as regards the secular, study-of religions based RE that I think ought be taught in public schools as a totally ordinary school subject and as such also true to its scientific basis. In what follows I map and evaluate some of the many approaches to RE as well as some of the obstacles to a study-of-religions approach. Likewise, I ever so briefly argue why my approach to RE may be seen as a 'natural' and 'good' kind of 'applied ASR ', as an obvious way to promote and strengthen the academic study of religions, --and as a positive value to the open, democratic and pluralistic society. I begin, however, with a statement by Prof. Brian Bocking, quoted in part below, which admirably describes the components and characteristics of the academic study of religions - and by extension - of a study-of- religions based RE.